2020
DOI: 10.3389/fpsyg.2020.01873
|View full text |Cite
|
Sign up to set email alerts
|

How Team Structure Can Enhance Performance: Team Longevity’s Moderating Effect and Team Coordination’s Mediating Effect

Abstract: Teams are more or less structured in function. Whether team structure is beneficial or harmful for the teams entail debates in current literature. Past studies mainly investigate the effects of team structure through learning or creativity. In this study, we tend to examine the effect of team structure on team performance through team coordination. We conducted two independent field studies with samples of 56 and 67 work teams to test our hypotheses. In both two substudies, we found team structure positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…This category includes factors relating to the team setup and structure such as team diversity, leadership, and team size. Ji and Yan (2020) found that team structure can improve team coordination.…”
Section: Factors That Affect Team Performancementioning
confidence: 99%
“…This category includes factors relating to the team setup and structure such as team diversity, leadership, and team size. Ji and Yan (2020) found that team structure can improve team coordination.…”
Section: Factors That Affect Team Performancementioning
confidence: 99%
“…Based on the presented research results, fluency in interacting with a cobot is the operator’s means to subjectively feel control over the situation. The feeling of control comes from the operator’s hands-on engagement and reliable input in the task fulfillment [ 40 ], his or her trust in the robot due to its reliability in contribution to the tasks [ 11 ], predictability [ 17 ], and fulfillment of expectations [ 45 ], and the synergic cooperation possible through team structure [ 11 ] and coordination [ 49 ]. Control over the situation and social support received from the collaborative robot [ 10 , 42 ] help counteract the adverse or challenging job demands and may lead directly to job satisfaction [ 86 , 88 ] for operators working in automated jobs [ 19 ] and to job performance, either directly [ 86 ] or indirectly through the enhancement of a positive affective-cognitive state of work engagement [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to directly capture team-oriented fluency [ 30 ], Paliga and Pollak [ 31 ] considered the team level of an automated system committed to fulfilling joint intentions [ 48 ] and performing together in a dyad [ 22 ] or team [ 17 ]. Specifically, effective team structure [ 11 ] and coordination [ 49 ] are the factors that facilitate fluent human-robot interactions [ 40 ]. Hence, team-oriented fluency refers to synchronous or sequential task performance [ 1 ] in a temporospatial overlap [ 14 ] by two (or more) mutually coordinated team members whose qualities should be utilized according to their advantages [ 50 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In contrast, Negative Conflict refers to disagreements expressed in a confrontational or destructive way (for example, we look each other in the face when we disagree). While these four dimensions vary widely within sports teams, they are related to team cohesion ( Sullivan and Short, 2011 ) and performance ( Ji and Yan, 2020 ). Confirmatory Factor Analysis (CFA) validated the scale with a sample of 251 athletes.…”
Section: Methodsmentioning
confidence: 99%